Interethnic Marriage Decisions: A Choice between Ethnic and Educational Similarities - Delia Furtado; Nikolaos Theodoropoulos (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2007)
This paper examines the effect of education on intermarriage and specifically, whether the mechanisms through which education affects intermarriage differ by immigrant generation and race. We consider three main paths through which education affects marriage choice. First, educated people may be better able to adapt to different customs and cultures making them more likely to marry outside of their ethnicity. Second, because the educated are less likely to reside in ethnic enclaves, meeting potential spouses of the same ethnicity may involve higher search costs. Lastly, if spouse-searchers value similarities in education as well as ethnicity, then they may be willing to substitute similarities in education for ethnicity when evaluating spouses. Thus, the effect of education will depend on the availability of same-ethnicity potential spouses with a similar level of education. Using U.S. Census data, we find evidence for all three effects for the population in general. However, assortative matching on education seems to be relatively more important for the native born, for the foreign born that arrived at a fairly young age, and for Asians. We conclude by providing additional pieces of evidence suggestive of our hypotheses.
Keywords: J12; I21; J61; 330; Ethnic intermarriage; Education; Immigration